The effect of rewarming on hemodynamic parameters and arterial blood gases of patients after open-heart surgery: A randomized controlled trial - Haji-Jafari, Somayeh; Rezaei, Mahboubeh; Azizi-Fini, Ismail; Tafti, Seyed Hossein Ahmadi; Atoof, Fatemeh (Journal of vascular nursing, 2023)
•Hypothermia can have potential side effects for patients with cardiac surgery.•Rewarming is effective in improving some hemodynamic parameters.•Rewarming can be used safely to improve the patients’ hemodynamic parameters after open-heart surgery. Hypothermia after open-heart surgery can have potential side effects for patients. This study aimed to examine the effects of rewarming on patients' hemodynamic and arterial blood gases parameters after open-heart surgery. This randomized controlled trial was performed in 2019 on 80 patients undergoing open-heart surgery at Tehran Heart Center, Iran. The subjects were consecutively recruited and randomly assigned to an intervention group (n=40) and a control group (n=40). After the surgery, the intervention group was warmed with an electric warming mattress while the control group warmed using a simple hospital blanket. The hemodynamic parameters of the two groups were measured 6 times and arterial blood gas was measured 3 times. Data were analyzed by independent samples t and Chi-squared tests, and repeated measures analysis. Before the intervention, the two groups did not significantly differ in terms of hemodynamic and blood gas parameters. However, the two groups were significantly different in the mean heart rate, systolic blood pressure, diastolic blood pressure, mean arterial blood pressure, temperature, right and left lung drainage in the first half-hour, and the first to fourth hours after the intervention (p < 0.05). Furthermore, there was a significant difference between the mean arterial oxygen pressure of the two groups during and after rewarming (P <0.05). Rewarming of patients after open-heart surgery can significantly affect hemodynamic and arterial blood gas parameters. Therefore, rewarming methods can be used safely to improve the patients’ hemodynamic parameters after open-heart surgery.